Answer:
yes, because (a+c) =b
Explanation:
Given that equation of the line is y=x.
B and C are two points lying on this line.
Midpoint of B and C are given as (a+c, b)
From this we see that using midpoint formula
![a+c=(x1+x2)/(2 ) and\\b=(y1+y2)/(2 )](https://img.qammunity.org/2019/formulas/mathematics/middle-school/gxaehy1yluejab6b59m00b19np3t99v98g.png)
Since both points lie on y=x, we get
x1=y1 and x2=y2
So x1 = a+c and 2y1 = 2b or y1 =b
Since x1=y1, we have a+c =b
i.e. the coordinates of mid point satisfy the equation y=x
Hence answer is
yes, because (a+c) =b